Power and errors in adverse impact indices. Issue 3 (26th May 2016) - Switzer, Fred S.; Roth, Philip L.; Rosopa, Patrick J.
ABSTRACT: Adverse impact indices are intended to detect potentially discriminatory employment practices, and although the number of such indices continues to increase, with a few exceptions, little is known about the comparative performance of those indices under various conditions. We examined the performance of eight such indices, including statistical significance tests, ad hoc "practical" tests proposed by the courts, and effect size measures. The power of these indices was examined under various levels of adverse impact, applicant pool sizes, and selection ratios. Although no index performed well in all circumstances, typically, Fisher's exact test and the Z test for proportions (with correction for continuity) performed adequately most often. However, in some conditions, these indices were outperformed by some of the "practical" tests.